House for E.B. Halsall, Esq., Oak Bay, Victoria, B.C. - http://id.worldcat.org/fast/175028 (1920)
468 Beach Drive, Oak Bay, B.C.; Item is an architectural drawing by Samuel Maclure prepared for E.B. Halsall of Victoria, B.C.; Plans, elevations, sections and details. One drawing shows wiring details. The house on the contract drawings has two-floors and a basement. This latter contains a furnace room, coal and wood bins, storerooms, laundry room, shower and dressing room and water closet. The ground floor includes a vestibule, hall, living room, dining room, breakfast room, kitchen, pantry, larder and veranda. Three bedrooms, bathroom, water closet and sleeping porch make up the second floor. Contract drawings inscribed: "This is one of the drawings referred to in our contract dated Aug. 27, 1920. [Signed] Kenneth B. Foyster [and] E B Halsall".